Genetic diversity and population structure of the endangered Rubus chamaemorus populations in Poland - Jacek Urbaniak; Paweł Kwiatkowski; Paweł Pawlikowski (Global Ecology and Conservation, 2023)
Rubus chamaemorus in Europe is currently only found in scattered sites in Central Europe, mainly in mountainous areas but also in lowlands, probably reflecting its relict nature. Unfortunately, so far, there is little information on the genetic diversity of R. chamaemorus populations in Central Europe. Therefore, in this study, we used genetic markers to investigate variation in 21 of its European populations. Using a Bayesian approach, STRUCTURE software analysis was applied to the six clusters that best represented the genetic structure of the cloudberry populations. The results indicated the presence of low genetic diversity between populations in geographical groups, but high diversity between geographical regions. These results were somewhat predictable because the vast lowlands that separate the mountains in Poland from the population of R. chamaemorus in the north are a significant geographical barrier to gene flow over long geographical distances. Isolation by distance may also explain the genetic distinctness between populations found in the various regions in Poland and populations found in Scandinavia. It is likely that there is a genetic melting pot for R. chamaemorus in the region of northern Poland. This is often the case in small areas where populations from different geographic regions meet. It is often difficult to indicate the migration routes of species and to confirm where individual populations come from, but their occurrence is favored by isolation in mountain valleys and in forests, which are a barrier to the spread of pollen.